Uhhleeah
Uhhleeah
21-01-2015
Mathematics
contestada
Let f(x) = 2x - 6. Solve f-1(x) when x = 2.
Respuesta :
superkoopasirf
superkoopasirf
21-01-2015
[tex]f(x) = 2x - 6 \\\\ ff^{-1}(x) = 2f^{-1}(x) - 6 \\\\ x = 2f^{-1}(x) - 6 \\\\ \implies f^{-1}(x) = \frac{x + 6}{2} \\\\\\ f^{-1}(2) = \frac{2 + 6}{2 } = \frac{8}{2} = \boxed{4}[/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 88+ )
Otras preguntas
The governor of a state can call-up the National Guard to protect lives and property in times of emergency because the state has authority to __________. declar
A book sold 35,700 copies in its first month of release. Suppose this represents 6.9% of the number of copies sold to date. How many copies have been sold to da
Where have some of the strongest and earliest impacts of global warming occurred?
Who constructed railroads
The ____________ act was passed in 2002 to tighten laws affecting business ethics.
The ability to put yourself in someone else's shoes and to feel with that person is known as _____.
Solve the equation 7X-11=19-3X What’s x ???
In protest against the sale of indulgences, who launched the protestant reformation in germany?
What is the length of AC 10 11 7 4
Eric divides a strip of paper into 8 equal parts.he cut off 2 of the parts. he shades 4 of the remaining whole does Eric shade blue?
ACCESS MORE